A randomized phase II study of weekly nab-paclitaxel plus gemcitabine or simplified LV5FU2 as first-line therapy in patients with metastatic pancreatic cancer: the AFUGEM GERCOR trial. Issue 1 (December 2015) - Bachet, Jean-Baptiste; Chibaudel, Benoist; Bonnetain, Franck; Validire, Pierre; Hammel, Pascal; André, Thierry; Louvet, Christophe
Abstract Background Metastatic pancreatic adenocarcinoma (PAC) prognosis remains dismal and gemcitabine monotherapy has been the standard treatment over the last decade. Currently, two first-line regimens are used in this setting: FOLFIRINOX and nab-paclitaxel plus gemcitabine. Increasing translational data on the predictive value of hENT1 for determining gemcitabine efficacy suggest that a non-gemcitabine-based regimen is favored in about 60 % of patients with PAC due to high resistance of PAC to this cytotoxic drug. This study aims to evaluate the efficacy of weekly nab-paclitaxel combined with gemcitabine or a simplified (s) LV5FU2 regimen in patients with previously untreated metastatic PAC. Methods/design AFUGEM is a two-stage, open-label, randomized, multicenter, phase II trial. Patients with PAC who meet the inclusion criteria and provide written informed consent will be randomized in a 1:2 ratio to either nab-paclitaxel (125 mg/m2 ) plus gemcitabine (1000 mg/m2 ) given on days 1, 8, and 15 every 28 days or nab-paclitaxel (125 mg/m2 ) plus sLV5FU2 (leucovorin 400 mg/m2 followed by bolus 400 mg/m2 5-fluorouracil and by 5-fluorouracil 2400 mg/m2 as an 46-h intravenous infusion) given on days 1 and 15 every 28 days. A total of 114 patients will be randomized to one of the treatment arms. The primary endpoint is progression-free survival at 4 months. Secondary outcomes are rate and duration of response, disease control, overall survival, safety, and quality of life. Potential biomarkers of gemcitabine (hENT1, dCK) and 5-fluorouracil (TS) efficacy will be assessed. Discussion The AFUGEM trial is designed to provide valuable information regarding efficacy and tolerability of nab-paclitaxel plus gemcitabine and nab-paclitaxel plus sLV5FU2 regimens. Identification of potential predictive biomarkers of gemcitabine and 5-fluorouracil is likely to drive therapeutic decisions in patients with metastatic PAC. Trial registration AFUGEM is registered at Clinicaltrials.gov:NCT01964534, October 15, 2013.